Nosocomial Infections in Patients with Traumatic Brain Injury: A Hospital-Based Study from North India - Koul, Ajaz; Sheikh, Arif; Bhat, Sajad; Ahad, Abrar; Qadir, Ruhail; Khurseed, Nayl; Kamil, Raja (Indian Journal of Neurosurgery, 2021)
Background Traumatic brain injury (TBI) is a major global health concern, it being a leading cause of morbidity and mortality in young adults. Infections acquired in the hospital setting are one of many risk factors that are associated with higher mortality in this population. Despite significant impact on the overall outcome, infections in TBI patients are largely understudied and underreported. The purpose of this study was to study the profile of infectious complications in patients with TBI and impact of these infections on the hospital outcome of these patients.Materials and Methods The medical records of all the patients with a diagnosis of TBI admitted in our hospital from January 2017 to January 2020 were reviewed. They were screened for presence of any predefined infection acquired at any time during their hospital stay. Data regarding demographics, focus of infection, results of various cultures, and hospital outcome was recorded.Results A total of 60 patients with TBI who had developed nosocomial infections were included in this observational study. Patients were mostly young, with a mean age of 36.6 years. Majority (66.6%) of patients who developed infectious complications had Glasgow coma scale (GCS) score of less than 10. Respiratory tract and urinary tract were the most common sites of infections in these patients. Burkholderia cepecia and Acinetobacter baumannii were the two most common isolated organisms. All-cause mortality in this population was 23.3%.Conclusions Most TBI patients are young, in their productive period of lives, and do not have major comorbidities. Invariably, they have low GCS scores and encounter a breach of their surface immunity due to catheters, procedures, and intubation. Such patients make an extremely significant impact on hospital resources as well as poor economic outcomes.
Keywords: traumatic brain injury; nosocomial infections; infections